PRODUCTION OF OIL PALM (Elaeis guineensis Jack) FLOWER BUNCHES IN ULTISOL ON APPLICATION OF BIOFERTILIZERS AND IN ORGANIC FERTILIZERS - Elis Kartika; Made Deviani Duaja; Gusniwati Gusniwat (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2022)
One of the efforts to increase the production of oil palm flower bunches in ultisols is applying biofertilizers and inorganic fertilizers. Biofertilizers can reduce the use and adverse effects of inorganic fertilizers. Arbuscular Mycorrhizal Fungi (AMF) is one of the biofertilizers that can help plants absorb nutrients and increase plant resistance to various environmental stresses. This study aimed to examine the role of AMF (as biofertilizer) and inorganic fertilizers in increasing the production of oil palm flower bunches in Ultisol. This experiment is a factorial experiment using a Randomized Block Design. The first factor is the application of biofertilizers, which consists of two levels without biofertilizers (AMF) and with biofertilizers (AMF). The second factor is the dose of inorganic fertilizer, composed of 5 levels, no inorganic fertilizer, 25, 50, 75, and 100% recommended doses of inorganic fertilizer. The variables observed were the number of sheaths, the percentage of broken sheaths, the number of male flower bunches, the number of female flower bunches, the percentage of male and female flower bunches, sex ratio per plant, and AMF colonization. The results showed that AMF biofertilizer saved 25% of inorganic fertilizers and increased 29.33% of female flowers production. The highest production of oil palm flower bunches was obtained from the application of AMF biofertilizer and 75% of inorganic fertilizers (1.5 kg Urea, 1.1 kg SP-36, 1.2 kg MOP, 0.7 kg Kisserite per plant). Oil palm with AMF had a higher average sex ratio than plants without AMF biofertilizers. The average sex ratio in oil palm plants applying AMF biofertilizer and inorganic fertilizers ranged from 0.42 to 0.73.